2020
DOI: 10.35366/94012
|View full text |Cite
|
Sign up to set email alerts
|

Conformación de póntico E en sector anterior.

Abstract: El póntico E es una alternativa de tratamiento para la pérdida prematura dental, este tipo de póntico fue publicado por primera vez en 2014 por Robert P. Korman. El diseño del póntico permite ofrecer predictibilidad en cuanto a soporte y mantenimiento de la arquitectura gingival, también promueve que el tejido vestibular migre coronalmente sobre el póntico, creando un surco gingival. Se recibió a una paciente que presentaba fragmento radicular del diente 21 y ausencia del diente 12, reborde residual atrófico (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
0
2
Order By: Relevance
“…In concordance with my survey, Gill et al (2012) found that Mordellidae were diurnal, and Elateridae were nocturnal. Similarly, Carabidae showed predominantly nocturnal activity in a Mexican study (Hernández-Camargo et al, 2017). This Mexican study revealed almost only nocturnal Scarabaeidae and predominantly diurnal Chrysomelidae, in contrast to my findings.…”
Section: Diel Activity In Relation To the Taxoncontrasting
confidence: 95%
See 1 more Smart Citation
“…In concordance with my survey, Gill et al (2012) found that Mordellidae were diurnal, and Elateridae were nocturnal. Similarly, Carabidae showed predominantly nocturnal activity in a Mexican study (Hernández-Camargo et al, 2017). This Mexican study revealed almost only nocturnal Scarabaeidae and predominantly diurnal Chrysomelidae, in contrast to my findings.…”
Section: Diel Activity In Relation To the Taxoncontrasting
confidence: 95%
“…I found that the proportions of nocturnal and diurnal individuals were balanced among the 23 canopy-tree species. In contrast to the Venezuelan study, Hernández-Camargo et al (2017) found that most of the 648 beetle specimens collected from 26 families were active at night (59.87%) in a tropical deciduous forest in Mexico. Unlike the number of Diel activity of adult beetle individuals collected with the window traps in the canopy on six tree species in a lowland rainforest canopy, Venezuela, between 1997 and 1999.…”
Section: Habitat Filteringcontrasting
confidence: 80%